Evidence of underdiagnosis and markers of high blood pressure risk in children aged 6 to 13 years - Jeanne Teixeira Bessa Fuly; Nayara Paula Bermudes Giovaninni; Daniele Gasparini Marcato; Eduardo Roberty Badiani Alves; Jéssica Dutra Sampaio; Leonardo Iezzi de Moraes; Thaís Coutinho Nicola; Julyanna Silva Araújo de Jesus; Everlayny Fiorot Costalonga (Jornal de Pediatria (Versão em Português), 2014)
Objective: To estimate the prevalence of high blood pressure (BP) in school children, as well as the reported frequency of previous measurements of BP in these children, and to identify high BP risk markers in the sample. Methods: This was a cross-sectional study involving 794 children aged 6 to 13 years, enrolled in public elementary schools. A questionnaire was given to parents/guardians, consisting of perinatal, socioeconomic data, and information on previous measurements of BP in these children. Anthropometric measurements included weight, height, waist, hip, and arm and neck circumference, in addition to the three BP measurements. Classification of BP levels was carried out according to current international recommendations, established in 2004. Results: The prevalence of high BP (hypertension or prehypertension) was 7%. Only 21.7% of children had previously undergone BP measurements. The odds ratio of high BP among children with and without overweight was 2.9 (95% CI = 1.7 to 5.0, p < 0.001). None of the anthropometric measurements was superior to the Z-score of BMI as a predictor of high BP. History of hypertension during pregnancy (p < 0.001), prematurity (p = 0.006), maternal hypertension (p = 0.01), and paternal hypertension (p = 0.008) were also correlated with the presence of high BP in children. Conclusions: Overweight and family history constitute the main risk markers of high BP in children. The low frequency of BP measurement in children observed in this municipality contributes to the underdiagnosis of the disease, with irreversible consequences for these individuals.